Morphological study of pulp cavity anatomy of canine teeth in domestic cats using micro-computed tomography - Chrostek, Emilia; Peralta, Santiago; Fiani, Nadine (Frontiers in Veterinary Science, 2024)
An understanding of the pulp cavity anatomy of individual teeth is essential for success during endodontic therapy. The objective of this study was to document pulp cavity anatomy and summarize numerical data of maxillary and mandibular canine teeth of domestic cats using micro-computed tomography (micro-CT). Thirty-nine canine teeth from eleven domestic cat cadaveric specimens were extracted and prepared for scanning. Segmentation of the pulp cavity was performed using the Avizo (v2022.2) software package. The morphological features of the pulp cavity including overall shape, configuration, presence of apical deltas and lateral canals was recorded. A quantitative analysis was performed on thirty-one teeth to explore associations between pulp cavity volume and length, apical delta length, maximum apical delta foramina number and cusp-to-tip length using a linear mixed model. Correlation between pertinent continuous variables was assessed using a Pearson's correlation test.Most pulp cavities exhibited varying curvature and ranged from a cylindrical configuration in the coronal third to an ovoid configuration in the middle to apical third. A ribbon-like flattened canal was observed in 6/31 teeth (19%). All canine teeth depicted an apical delta with various configurations except for two teeth that showed a single canal exiting at the apex. In 15/31 teeth (48%), the primary root canal within the apical delta could be clearly identified and in 16/31 (52%) the primary root canal was indiscernible. The results showed that the pulp cavities of maxillary canine teeth were significantly larger and longer and the cusp-to-tip length was longer, when compared to mandibular teeth. The apical delta length was negatively correlated to the volume of the pulp cavity. No specimens depicted lateral canals. This study revealed that the anatomy of the canine tooth pulp cavity in cats can vary considerably and should be a consideration when performing thorough debridement, shaping and obturation of the endodontic system.